Numerical analyses for improved terminal velocity of deep water torpedo anchor - Soh, B. (Emerald Group Publishing Ltd., 2017)
Purpose - This research aims to investigate the effects of manipulation of a torpedo's geometries to attain higher terminal velocity. The parameters of interest include geometric changes of the original design, as well as sea water properties that reflect water depth in South China Sea. Design/methodology/approach - The research make use of computational fluid dynamics (CFD) software, FLUENT, to solve viscous incompressible Navier-Stokes equations with two equations k-epsilon turbulent model. The calculated drag coefficient is subsequently used to calculate the maximum attainable terminal velocity of the torpedo. Findings - It was found that the terminal velocity can be improved by sharper tip angle, greater aspect ratio, greater diameter ratio and optimum rear angle at 30°. Sensitivity of drag coefficient toward each of the parameters is established in this paper. Originality/value - The paper, in addition to verifying the importance of aspect ratio, has also established the tip angle, diameter ratio and rear angle of the torpedo as important geometric aspects that could be tuned to improve its terminal velocity. © Emerald Publishing Limited.